تأثير تمرينات بوسائل مبتكرة لتطوير دقة المناولة العميقة بأنواعها للاعبين الأشبال بكرة القدم - اللامي، غيث عبدالله حسين (جامعة القادسية - كلية التربية الرياضية, 2016)
تجلت مشكلة البحث فهي ملاحظة الباحث أن أغلب اللاعبين الأشبال في نادي الديوانية الرياضي لديهم ضعف في أداء المهارات الأساسية وفي مقدمتها المناولة وخصوصا المناولة العميقة وكذلك لاحظ الباحث قلة عناية بعض المدربين باستخدام الوسائل التدريبية الحديثة والمبتكرة التي ممكن أن تطور هذا الضعف المهاري أما أهداف البحث هي إعداد تمرينات بوسائل مبتكرة لتطوير المناولة العميقة بأنواعها للاعبين الأشبال بكرة القدم والتعرف على تأثير التمرينات المقترحة بوسائل مبتكرة (المجموعة التجريبية). أما فروض البحث فكانت : هناك فروق ذات دلالة إحصائية بين الاختبارين القبلي والبعدي للمجموعة التجريبية في دقة بعض إشكال المناولة وان التمرينات المقترحة التي اعدها الباحث بوسائل مبتكرة للمجموعة التجريبية هو الأفضل في دقة المناولة العميقة بأنواعها، أما المجالات فهي : المجال البشري: اللاعبون الأشبال في نادي الديوانية الرياضي للفئة العمرية من (12-14) سنة، المجال المكاني: ملعب نادي الديوانية، المجال الزماني 2012-0-2015 ولغاية 2015-5-20، أما الفصل الثالث فقد احتوي علي منهجية البحث، فقد استخدم الباحث المنهج التجريبي بطريقة المجموعة الواحدة لملائمته طبيعة المشكلة وتضمن وصفا لمجتمع البحث التحليلات الإحصائية وعينته، وتم تطبيق منهج البحث بأشراف الباحث وبعد تطبيق التمرينات المقترحة بوسائل مبتكرة تم إجراء التحليلات الإحصائية الاستخراج نتائج البحث، كما أشتمل الفصل الرابع على عرض النتائج وتحليلها ومناقشتها بشكل علمي لتحقيق فروض البحث وصولا للنتائج العلمية أما الفصل الخامس فتضمن الاستنتاجات والتوصيات، فكانت اهم الاستنتاجات: أن التمرينات بوسائل مبتكرة كان له الأثر متعددة من المهارات في كرة القدم والتعرف على فاعليتها في تللك المهارات.
Demonstrated problem Find it Note researcher said most players Cubs in Diwaniya sports club have weakness in the performance of the basic skills, particularly the handling, especially the deep handling as well as the researcher noted the lack of attention to some of the coaches using modern training methods and innovative as possible that this weakness skill development either research objectives is to prepare exercises innovative means for the development of deep handling all kinds of players Cubs football and identify the impact of exercises proposed innovative means) of the experimental group (. either hypotheses were: There were statistically significant differences between pre and post tests the experimental group in the accuracy of some forms of handling and that the proposed exercise prepared by researcher innovative means of experimental group is the best in handling all kinds of deep accuracy, either areas are: the human sphere: Cubs players in Diwaniya sports club age group) 12-14 years), the spatial domain: Stadium Club Diwaniyah, field temporal 12/02/2015 to 20 -5-2015, The third chapter contains the research methodology, the researcher used the experimental method in a way one group of suitability nature of the problem and included a description of the research community and appointed, was the application of research methodology under the supervision of a researcher and after the application of the proposed exercises innovative means was performed statistical analyzes to extract search results , also included the fourth quarter to show the results analyzed and discussed in a scientific manner to achieve the hypotheses access to scientific results, either Chapter V guarantees the conclusions and recommendations, was the most important conclusions: that exercise innovative means has had a positive impact in the development of deep kinds handling accuracy, either the most important recommendations are: the use of innovative means by the researcher in the education of multiple types of skills in football and get to know its effectiveness in those skills.
Keywords: التربية البدنية -- التربية الرياضية -- كرة القدم -- التمرينات الرياضية